The Role of Schools in Early Marriage Education and Reproductive Health Rights (Case Study: Students in Wonosobo District) - M Junaedi; L Muntaqo; S Haryanto; A Khoiri; N K Khanifa (STAI Hubbulwathan Duri, 2022)
The role of schools is an important factor in shaping human civilization. The phenomenon of the high number of high school marriages in Wonosobo with all the social changes that surround it, until 2019 marriages under the age of 19 (nineteen) years there were 430 cases including marriage dispensation. The Merried By Accident (MBA) case dominates all of these cases. The focus of this research is the analysis of the role of school in child marriage and women's reproductive rights, two things that influence each other and whether women's reproductive health rights include the right to abortion and to refuse pregnancy which often occurs in society. This study uses qualitative research by conducting in-depth interviews and discussion group forums which are analyzed and described using a symbolic interactionism approach. The results of the study found that there was a shift in the meaning of marriage for high school children, the high number of cases of child marriage was dominated by changes in social behavior and adolescent relationships, so that pregnancy before marriage led to dropping out of school. Women's reproductive health rights are especially not ready to give birth, take care of children so that the life cycle after giving birth to children does not get serious attention, and it is not uncommon for domestic violence (KDRT) to be a way out to solve problems that cause divorce at a young age. The role of schools has not shown significant results because there is almost no curriculum in schools that requires provisions about marriage. The ideal school role is in the form of providing early marriage education and reproductive health, having an effective school fee subsidy, providing regular health services, and motivating students in the spirit of learning at school.